Development of Mathematical Creative Thinking Skills in Elementary School Students through the GASING Method - Titin Usmar; Turmudi Turmudi (Journal of Educational Sciences, 2026)
The demand for higher-order thinking skills is increasing, and mathematical creativity must be developed systematically from the elementary level. This study aims to examine the development of students’ mathematical creative thinking through the GASING method (Fun, Easy, and Enjoyable Learning). This study used a quantitative quasi-experimental design with a pretest-posttest approach on a selected group. The limitation of this study lies in the small sample size (20 students) and the use of purposive sampling limits the generalizability of the findings; therefore, further studies with larger samples are needed to validate the results. The instrument was a mathematical creative thinking test covering fluency, flexibility, originality, and elaboration. Data were analyzed using descriptive statistics and the N-Gain test. The results show that the average score improved from 30.95 (pre-test) to 64.95 (post-test), with an N-Gain of 0.4827 (48.27%), categorized as moderate. The highest improvement occurred in fluency (29 to 84), followed by originality (25 to 63), elaboration (31 to 67), and flexibility (26 to 60). While gains in originality and elaboration suggest that the concrete-to-abstract approach deepens students’ creativity, overall, these findings indicate that the GASING method is effective in improving elementary students’ mathematical creative thinking skills.